Model Pemberdayaan Masyarakat Dalam Melaksanakan 5 Pilar STBM Di Sorowajan Bantul - Kasjono, Heru Subaris; Widyantoro, Wahyu; Pujiyati, Nunuk Endang (Universitas Muhammadiyah Surabaya, 2017)
Challenges related to health development, particularly in the field, hygiene and sanitation are still great need to be undertaken integrated interventions through a Total Community Based Sanitation approach or commonly known as STBM. According to the PHBS survey that has been done by Puskesmas Sewon II in 2014 in Sorowajan result 21.71% of citizens who have maintained healthy healthy behavior according to indicator 10 indicator PHBS so that still in low category. Community service is done STBM approach implemented in the working area of Puskesmas Sewon II that is in Sorowajan hamlet, Panggungharjo village, Sewon district, Bantul district, DI Yogyakarta. The purpose of this empowerment activity is to raise awareness in the five pillars of STBM. The method used is to model the modified STBM trigger. After carrying out community empowerment in the implementation of 5 pillars of STBM After carrying out community empowerment in application of 5 pillars of STBM to help accelerate Sorowajan area become hamlet that qualified STBM. The results of the survey after the launch activities of 5 pillars STBM trigger as much as 97.28% with a 75.57% increase. These results show the STBM triggering model is able to increase the poverty of PHBS in Sorowajan village.